Morphology of Immatures of Acanthoderini (Cerambycidae, Lamiinae) - Casari, Sônia A. (Zootaxa, 2016)
Morphological descriptions and comparisons of immatures of five species of Acanthoderini are presented. Larvae and pupae of Psapharochrus cylindricus (Bates, 1861) and P. vetustus (Bates, 1880), larva of P. jaspideus (Germar, 1824), and pupae of Oreodera glauca (Linnaeus, 1758) and Steirastoma stellio Pascoe, 1866, from Brazil, are described; larvae of the two latter species are redescribed. Until now, immatures of 20 species of this tribe were known. Remarks on characters in Acanthoderini and genera with known immatures are also included.